2019
DOI: 10.1080/09593985.2019.1622162
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy treatment experiences of persons with persistent musculoskeletal pain: A qualitative study

Abstract: The aim of this study was to explore and describe the physiotherapy treatment experiences of persons with persistent musculoskeletal pain. Eleven participants with persistent musculoskeletal pain in the back, neck, or shoulders were included in the study. Data was collected via semistructured interviews and were analysed with qualitative content analysis. The analysis resulted in the theme "Towards acceptance and management of pain", comprising four sub-themes: 1) Establishing and maintaining a therapeutic all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…This aligns with other research on establishing a therapeutic alliance in physiotherapy involving patients with chronic pain disorders [19,22,33,36,52]. In 2019, Calner et al [56] interviewed persons with persistent musculoskeletal pain and found that the alliance between the physiotherapist and the patient must be built on initial trust, a continuous dialogue, and clear communication. This finding is consistent with that of O'Keefe et al [35] and Slade et al [57], who found that the alliance factor is an element that can enhance treatment outcomes.…”
Section: Discussionsupporting
confidence: 67%
“…This aligns with other research on establishing a therapeutic alliance in physiotherapy involving patients with chronic pain disorders [19,22,33,36,52]. In 2019, Calner et al [56] interviewed persons with persistent musculoskeletal pain and found that the alliance between the physiotherapist and the patient must be built on initial trust, a continuous dialogue, and clear communication. This finding is consistent with that of O'Keefe et al [35] and Slade et al [57], who found that the alliance factor is an element that can enhance treatment outcomes.…”
Section: Discussionsupporting
confidence: 67%
“…In this context of suffering, clinicians should help participants to increase their self-efficacy and develop appropriate coping strategies. 55 …”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapy provides a well-documented and important benefit in the management of musculoskeletal pain, although it requires sustained effort on the part of the patient. 74 Stretch exercises to improve flexibility can help limit musculoskeletal pain by preventing repetitive strain and musculoskeletal injuries and improve mobility as shown in a single-blind 12-week research study. 75 Regarding posture, every individual has a unique postural force/torque signature and muscle coordination strategies that induce differing degrees of mechanical wear of their musculoskeletal systems which may increase the risk of developing musculoskeletal disorders for some individuals.…”
Section: Mobility/flexibilitymentioning
confidence: 99%